KREDIBILITAS PRIBADI GEMBALA DALAM PERTUMBUHAN GEREJA - Johannes S.P Rajagukguk (Diegesis : Jurnal Teologi, 2019)
Shepherd as church leader is one of the determinants of the development of the church he leads. Inevitably, a church leader must possess, maintain and enhance his personal credibility (quality) from time to time. The personal credibility of a leader should give high marks to every leader in the eyes of those who are led and those around the group they lead. The personal credibility of a qualified shepherd should be able to develop the church organization he leads. To be able to say that a leader or pastor has high credibility must be seen from a variety of factors, such as his personality, communication skills, social relationships, competence and others.